**Algebra Puzzle**at: http://www.mathplayground.com/algebra_puzzle.html

- There are 2 levels.
- Attempt the
**3x3 grid**until you are able to find the solution of the puzzle. - Present your solution (together with the screen capture that shows the answers are correct)
__in your personal blog__. - Label the Blog post as "
**Chapter 4: Algebra Puzzle**" - Post the
**permlink**of your post to*comments*in this post. - The
**3x4 grid**is a bonus level... It is not compulsory, do challenge yourself to see if you could solve it using algebra (see example below)

- Find the value of each of the three objects presented in the puzzle.
- The numbers given represent the sum of the objects in each row or column.
- Sometimes, only one object will appear in a row or column.
- That makes the puzzle easier to solve. Other times, you will have to look for relationships among the objects.

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~

**Here is an example of how you should articulate your solutions in your personal blog**

**The 3 x 3 Grid puzzle**

__My solution__(

__Method 1__, which most of you would use this method to reason out/deduce your answer):

- 3 Apples = 6
**Therefore, 1 Apple represents 2**- 1 Apple + 2 Cars = 4
- Since 1 Apple represents 2,
- 2 + 2 Cars = 4
- 2 Cars represent 2
**Therefore, 1 Car represents 1**- 2 Apples + 1 Pen = 20
- Since 1 Apple represents 2, 2 Apples = 4
- 4 + 1 pen = 20
**Therefore, 1 Pen represents 16**

__My solution__(

__Method 2__, using the algebraic method which you will learn in Chapter 6, in Term 2):

- Let a represents apple
- Let c represents car
- Let p represents pen
- 3a = 6
- a = 6/3
- Therefore,
**a = 2** - Since 2a + p = 20
- 2(2) + p = 20
- 4 + p = 20
- p = 20 - 4
- Therefore,
**p = 16** - Since c + 2a = 5
- c + 2(2) = 5
- c + 4 = 5
- c = 5 - 4
- Therefore,
**c = 1**

**Bonus Level (We will only cover this method in next year):**

- Let m represents ice-cream
- Let p represents pear
- Let f represents flower
- 2m + p = 24 {equation #1}
- m + 2p = 45 {equation #2}
- From equation #2, we can say m = 45 - 2p
- Substitute it into equation 1, we get 2(45 - 2p) + p = 24
- We get 90 - 4p+ p = 24
- 90 - 3p = 24
- - 3p = 24 - 90
- - 3p = - 66
- Therefore,
**p = 22** - m = 45 - 2(22)
- Therefore,
**m = 1** - 2m + f = 26
- 2(1) + f = 26
- 2 + f = 26
- f = 26 - 2
- Therefore,
**f = 24**

http://siddharth98.blogspot.com/2011/03/chapter-4-algebra-puzzle.html

ReplyDeleteer.. for the second one there is a easier method...

ReplyDelete